Management of Archiving Incoming and Outgoing Letters at the Youth and Sports Office of North Sumatra Province - Mutia Sari; Muhammad Irwan Padli Nasution (Penerbit Jurnal Indonesia, 2022)
In an agency correspondence is an important means of communication. So that a process in correspondence must be considered in detail or detail because the large number of incoming and outgoing letters every day can create a pile of archives. This study aims to determine how the management of archiving incoming and outgoing mail. The research method used is descriptive qualitative. The informants in this study were 2 (two) employees of the Head of the General Subdivision (TU) and 1 (one) employee of the Sports Achievement Improvement section taken by purposive sampling technique. The results in this study indicate that the management of archiving incoming and outgoing letters has followed the SOP (Standard Operational Procedure) that already exists at the Youth and Sports Office of North Sumatra Province.